2021
DOI: 10.1109/tcyb.2019.2925015
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sigmoid-Function-Based Adaptive Weighted Particle Swarm Optimizer

Abstract: In this paper, a novel particle swarm optimization (PSO) algorithm is put forward where a sigmoid-functionbased weighting strategy is developed to adaptively adjust the acceleration coefficients. The newly proposed adaptive weighting strategy takes into account both the distances from the particle to the global best position and from the particle to its personal best position, thereby having the distinguishing feature of enhancing the convergence rate. Inspired by the activation function of neural networks, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 217 publications
(94 citation statements)
references
References 36 publications
(57 reference statements)
0
66
0
Order By: Relevance
“…In particular, the modified GAN has shown better performance than the conventional GAN. In our future work, we aim to: 1) develop an automatic hyperparameter selection scheme for GAN-based crack detection system based on evolutionary computation [31][32][33][34][35][36][37]; 2) apply our crack detection system to other thermography NDT tasks; 3) design a novel control strategy to enhance the detection performance of the crack detection system [38][39][40][41][42][43][44][45][46]; and 4) explore the dynamic behavior of the ECPT-based NDT process and study the thermography features based on signal processing and control theory [47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the modified GAN has shown better performance than the conventional GAN. In our future work, we aim to: 1) develop an automatic hyperparameter selection scheme for GAN-based crack detection system based on evolutionary computation [31][32][33][34][35][36][37]; 2) apply our crack detection system to other thermography NDT tasks; 3) design a novel control strategy to enhance the detection performance of the crack detection system [38][39][40][41][42][43][44][45][46]; and 4) explore the dynamic behavior of the ECPT-based NDT process and study the thermography features based on signal processing and control theory [47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…13. The optimal makespan comparison between two kinds of methods deep learning within different cooperation environment and various agent types for various targets [6], [25]; 2) solving the uncertain task allocation problem in a dynamic environment by using some novel optimization methods [2], [10], [35]- [38], [53]; and 3) the task allocation problem on MASs subject to engineering-oriented complexities [40], [46], [59], [62]- [64].…”
Section: Discussionmentioning
confidence: 99%
“…Experiment results have shown that the improved GAN outperforms the standard GAN for reconstructing the magnetic optical images, and the developed GAN-based crack detection method has demonstrated satisfactory performance in detecting the cracks in magnetic optical images. In the future, we aim to (1) employ our proposed GANbased crack detection for other NDT methods such as thermal imagery detection, ultrasound detection and X-ray imaging detection; (2) deploy evolutionary computation methods to optimize the parameter selection in the GAN-based crack detection system [24][25][26][27]; (3) employ signal processing and state estimation methods to investigate the stability of the NDT process [17,[19][20][21]28,34,35,42,46,54]; and (4) design an advanced control strategy to improve the detection accuracy and detection rate of the GAN-based crack detection system [14,18,33,47,50,52,55,56].…”
Section: Discussionmentioning
confidence: 99%